2004
DOI: 10.1002/art.20117
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of bone loss in patients with rheumatoid arthritis by long‐term high‐intensity exercise: Results of a randomized, controlled trial

Abstract: Objective. Patients with rheumatoid arthritis (RA) are more at risk for the development of osteoporosis and osteoporotic fractures than are their healthy peers. In this randomized, controlled, multicenter trial, the effectiveness of a 2-year high-intensity weight-bearing exercise program (the RheumatoidArthritis-Patients-In-Training [RAPIT] program) on bone mineral density (BMD) was compared with usual care physical therapy, and the exercise modalities associated with changes in BMD were determined.Methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 40 publications
2
46
0
6
Order By: Relevance
“…13 There was a non-significant trend to less bone loss at the hip in the RAPIT group versus usual care (-1.1% versus -1.9%, p=0.06), and no difference between the groups for bone density in the spine (+0.9% versus +0.9%, p=0.697). However when analysed by mixed-effect ANOVA, the mean between-group difference in change of hip BMD over the 2 years was statistically significant (p=0.026) in favour of the RAPIT group.…”
Section: Aerobic / Strength Combinationsmentioning
confidence: 83%
See 3 more Smart Citations
“…13 There was a non-significant trend to less bone loss at the hip in the RAPIT group versus usual care (-1.1% versus -1.9%, p=0.06), and no difference between the groups for bone density in the spine (+0.9% versus +0.9%, p=0.697). However when analysed by mixed-effect ANOVA, the mean between-group difference in change of hip BMD over the 2 years was statistically significant (p=0.026) in favour of the RAPIT group.…”
Section: Aerobic / Strength Combinationsmentioning
confidence: 83%
“…Some studies also reported improvements in disease activity measures 15,19,20,25 , and small improvements in hip bone mineral density. 13,16 One study reported significantly less progression of small joint radiographic damage of the feet in the dynamic exercise group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beginning physical activity can also reduce the risk of osteopenia and bone mass loss. [111][112][113] Brazilian guidelines for assessment, prevention and treatment of osteoporosis in patients with RA are urgently needed. In the initial assessment, bone densitometry should be indicated for all patients over the age of 50 years.…”
Section: Osteoporosismentioning
confidence: 99%